EFFECT OF HUMIC ACID CONCENTRATION AND SPRAYING STAGES ON SEEDS YIELD AND ITS CONPONENTS OF ALFALFA - Khrbeet, H. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was conducted at the experimental fields in the collage of Agricultural Engineering Sciences, University of Baghdad, Iraq during the period from mid. March 2019 to to end of July 2020. The main objective was to find out the effect of humic acid (HA) concentration (0, 1, 2 and 3 cm3.L-1) and three stages of foliar application (vegetative, growth, flowers buds emergence and 50% flowering) on seeds yield and its components of alfalfa local variety. Layout of the experiment was R.C.B.D arranged in split-plot, with three replications. Foliar application stages were used as main-plots, while humic acid concentrations were used as sub-plots. Results showed that spraying of HA at conc. 3 cm3.L-1 resulted in a significant increment in number of florets per raceme and number of pods per raceme, in contrast, % of florets abortion in and 1000 seeds weight were not significantly influenced by HA conc. and spraying stages. Highest number of the stems.m-2, number of racemes per stem, seed set and seeds yield (441.0) Kg.ha-1 were obtained from plants sprayed with HA at conc. 3 cm3.L-1. Plants sprayed at vegetative growth produce highest number of stems.m-2 number of raceme per stem, number of seeds per pod and seeds yield (423.6) Kg.ha-1. There was high positive correlation between seeds yield and each of, number of stems.m-2, number of pods per raceme and number of raceme per stem (+0.88**, +0.70** and +0.82**) respectively. There was a significant interaction between HA concentration and spraying stages on seeds yield. The higher seeds yield (485.) Kg.ha-1 was obtained when alfalfa plants were sprayed with HA at the conc. of 2 cm3.L-1 in vegetative growth.